Transmembrane Communication: General Principles and Lessons from the Structure and Function of the M2 Proton Channel, K(+) Channels, and Integrin Receptors - Grigoryan, Gevorg (2011)
Signal transduction across biological membranes is central to life. This process generally happens through communication between different domains and hierarchical coupling of information. Here, we review structural and thermodynamic principles behind transmembrane (TM) signal transduction and discuss common themes. Communication between signaling domains can be understood in terms of thermodynamic and kinetic principles, and complex signaling patterns can arise from simple wiring of thermodynamically coupled domains. We relate this to functions of several signal transduction systems: the M2 proton channel from influenza A virus, potassium channels, integrin receptors, and bacterial kinases. We also discuss key features in the structural rearrangements responsible for signal transduction in these systems.